Methodology for assessing the sustainability of hollow fiber membrane system for wastewater treatment - Mahmood, Salwa (2016)
The world’s supply of fresh water is finite and threatened by pollution such as the wastewater discharged from industries. Lately, the use of membrane system has received increasing attention for wastewater treatment. Though the membrane performance are usually determined, its performance from the sustainability perspective has received less attention. In line with the Malaysian government policy, the membrane system used for wastewater treatment needs to be scrutinized to ensure its sustainability according to the Triple Bottom Line aspects including environmental, social and economic. Previously, several tools or frameworks have been developed for assessing sustainability. However, most of the available tools assess membrane usage phase only without considering other phases of life cycle. This research aims to identify influencing parameters for assessing the sustainability of hollow fiber membrane system for wastewater treatment. In addition, a methodology for assessing the sustainability of membrane system was developed using fuzzy logic approach. It enables the assessment in the range between sustainable and non-sustainable membrane system. Life Cycle Assessment model was also developed to analyze the environmental burdens on the membrane system. GaBi software was employed to identify the parameters involved that cross the system boundary. The system boundary selected was from cradle-to-grave which consists of materials, fabrication process, transportation, usage and end of life phases. There were 29 parameters selected in the analysis. A Graphical User Interface was constructed using MATLAB platform, which was embedded with fuzzy linguistic calculation. A case study consists of a typical membrane system was successfully assessed by using the developed methodology. The results indicated that the sustainability level of the hollow fiber membrane module was high with an overall index value of 0.73. Fabrication process phase needs more attention in terms of sustainability as its index values were 0.27, 0.31, and 0.58 for environmental, social, and economic, respectively. For validation purposes, the results of the assessment were compared with the existing methodologies called ReCiPe and EcoIndicator99. However, the result from ReCiPe approach was limited to environmental aspect only. As for the social aspect, the findings were compared with the EcoIndicator99 approach. The results showed that the fuzzy evaluation method is able to assess the sustainability level of membrane system at par with the one obtained from EcoIndicator99.